Christian Faith Formation and Spiritual Insecurity in Africa - Moyo, Masauso; Pali, Joseph K. (Diligentia: Journal of Theology and Christian Education, 2025)
As early as 1930s Audrey Richards hinted at the irony that the spread of Christianity in Zambia, against all its good intentions, instead of diminishing fear, rather increased spiritual insecurity among its converts. There is scholarly evidence that the detected spiritual insecurity in the early 20th century persists up to now. The triggers of spiritual insecurity in Africa are attributed to the breakdown of traditional relationships and mutual obligation, the belief in the influence of the spirits on people for either good or bad. Spiritual insecurity shows that some of the Africans are in dilemma of Christian and African spiritual worldviews thereby struggling to fully trust the Christian approach to spiritually related challenges. This article validates the view that spiritual insecurity in Africa though highly ignored, should be taken seriously. It explores how the Church can use its faith formation system to address issue causing spiritual insecurity in Africa. Data collected through qualitative literature review and observations is engaged using the hermeneutical theory to argue for a faith formation which addresses the fissure between words about God in statements of faith and spiritual insecurity among African Christians by clarifying Christian confessions, identity and reflection.